Dendrobathypathes grandis Opresko 2002 ... - Lima, Manuela M.; Cordeiro, Ralf T. S.; Perez, Carlos D. (Zenodo, 2019)
Dendrobathypathes grandis Opresko, 2002 Fig. 35 Dendrobathypathes grandis Opresko, 2002: 427–431, figs. 9, 10, 11; Opresko, 2005: 141; Lauretta & Penchaszadeh, 2017: 109–114. Type and type locality. USNM 100114 (holotype): 54º28’58.8”S, 39º21’57.6”W, South Atlantic, South Georgia Island, 659–686 m; USNM 100131 (paratype): 53º19’58.8”S, 42º42’0”W, South Atlantic, South Georgia Island, 417–514 m. Diagnosis. Corallum sparsely branched; densely pinnulate; stem, branches, and primary pinnules generally in one plane; secondary pinnules on each primary pinnule extending out laterally on one side of the plane containing the primary pinnules and stem. Primary pinnules arranged alternately along the stem and branches in two anterolateral rows. Secondary pinnules arranged mostly uniserially on front side of primary pinnules; biserial arrangement occurring distally on the largest primaries. Tertiary and quaternary pinnules, when present, arranged uniserially on front side of the lower order pinnules. Spines simple ... : Published as part of Lima, Manuela M., Cordeiro, Ralf T. S. & Perez, Carlos D., 2019, Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic, pp. 1-67 in Zootaxa 4692 (1) on page 46, DOI: 10.11646/zootaxa.4692.1.1, http://zenodo.org/record/3528942 ...